2006
DOI: 10.1557/proc-0924-z08-31
|View full text |Cite
|
Sign up to set email alerts
|

Elastodynamic Characterization of Imprinted Nanolines

Abstract: The advancement of imprint lithography as a method for fabricating nanostructures is impeded by a lack of effective tools for characterizing mechanical properties and geometry at the nanoscale. This paper describes progress in establishing methods for determining elastic moduli and cross sectional dimensions of imprinted nanolines from Brillouin light scattering (BLS) measurements using finite-element (FE) and Farnell-Adler models for the vibrational modes. An array of parallel nanoimprinted lines of polymethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Hartschuh et al [5] and Johnson et al [8] presented Farnell-Adler calculations for Rayleigh-like and Sezawa-like modes that neglect the finite widths of nanolines, approximating them as blanket films with a thickness equal to the height of the nanolines. Despite the crudeness of this approximation, the frequencies from such calculations were found by these authors to be fairly close to frequencies measured with BLS, at least for the geometries considered, and the correspondence with measurements provided insight into the general form of the strain fields of the modes.…”
Section: Application To Nanolinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hartschuh et al [5] and Johnson et al [8] presented Farnell-Adler calculations for Rayleigh-like and Sezawa-like modes that neglect the finite widths of nanolines, approximating them as blanket films with a thickness equal to the height of the nanolines. Despite the crudeness of this approximation, the frequencies from such calculations were found by these authors to be fairly close to frequencies measured with BLS, at least for the geometries considered, and the correspondence with measurements provided insight into the general form of the strain fields of the modes.…”
Section: Application To Nanolinesmentioning
confidence: 99%
“…Inversion analysis of BLS spectra from imprinted polymethyl methacrylate (PMMA) nanolines was pursued by Johnson et al [8] using Farnell-Adler models, including an approximate correction for the effect of finite nanoline height on the flexural frequencies. The elastic constants and nanoline dimensions determined from this analysis were found to be physically unrealistic, presumably because of inaccuracies arising from the approximation of a blanket film in the models for the Rayleigh-like and Sezawa-like modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inversion analysis of BLS spectra from imprinted poly(methyl methacrylate) (PMMA) nanolines was pursued by Johnson et al [8] using Farnell-Adler models. One conclusion of that work was that relatively poor fitting of the calculations to the BLS data can be attributed to inaccuracy of the gross approximation of a blanket film in the Farnell-Adler models for the Rayleigh-like and Sezawa-like modes of the nanolines.…”
Section: Introductionmentioning
confidence: 99%
“…For example, very different dimensional and stiffness parameters were extracted from fits with and without the Sezawa-like mode included. Johnson et al [8] suggested that FE methods could overcome this problem to provide more accurate nanoline parameters.…”
Section: Introductionmentioning
confidence: 99%